2015
DOI: 10.1002/cctc.201501020
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Synthesis of Gold‐Nanoparticle‐Embedded, Nitrogen‐Doped Nanoporous Carbon Nanoparticles (Au@NC) with Enhanced Reduction Ability

Abstract: A de novo synthesis of gold nanoparticles embedded, nitrogen doped nanoporous carbon nanoparticles (Au@NC) was synthesized in this work. The chloroauroic acid was encapsulated inside zeolitic imidazolate framework-8 (ZIF-8) nanoparticles during the synthesis and later reduced into gold nanoparticles. The as-synthesized gold nanoparticles embedded ZIF-8 (Au@ZIF-8) was then carbonized into Au@NC to enhance the stability of the nanoporous support. The results showed that Au@NC exhibited a porous structure contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 60 publications
(58 reference statements)
3
25
0
Order By: Relevance
“…Introducing reactive gas and sputter systems, which allow manipulation of energies and chemical state of the sputtered atoms/clusters, for doping multiple metal NPs and for synthesizing desired compounds and structures can be also considered for sputtering onto liquids towards advanced nanomaterials. Regarding production of metal, metal alloy and hybrid nanoparticles with wide variety of morphologies, higher ordered structure, doping and functionalization, we have demonstrated that our solution synthesis approaches based on chemical reduction, plasma in liquid process and stabilizing agents are very versatile [120][121][122][123][124][125][126] though in many cases toxic chemicals and by-products are present as they are also expected in other reports. Hence, we encourage and welcome other researchers join investigating this new vacuum sputtering onto liquid method, take all of its great advantages as the green technique for pure nanoparticles and unexpected structures, as well as devote new ideas for achieving more versatile control of the sputtered NPs.…”
Section: Summary and Prospectssupporting
confidence: 59%
“…Introducing reactive gas and sputter systems, which allow manipulation of energies and chemical state of the sputtered atoms/clusters, for doping multiple metal NPs and for synthesizing desired compounds and structures can be also considered for sputtering onto liquids towards advanced nanomaterials. Regarding production of metal, metal alloy and hybrid nanoparticles with wide variety of morphologies, higher ordered structure, doping and functionalization, we have demonstrated that our solution synthesis approaches based on chemical reduction, plasma in liquid process and stabilizing agents are very versatile [120][121][122][123][124][125][126] though in many cases toxic chemicals and by-products are present as they are also expected in other reports. Hence, we encourage and welcome other researchers join investigating this new vacuum sputtering onto liquid method, take all of its great advantages as the green technique for pure nanoparticles and unexpected structures, as well as devote new ideas for achieving more versatile control of the sputtered NPs.…”
Section: Summary and Prospectssupporting
confidence: 59%
“…In the former case, small and naked NPs are typically embedded in the cavities, however, in the case of encapsulation, usually pre‐synthesized NPs are stabilized with surfactants or capping agents and hydrodynamic radius of the NPs is much larger than the cavity size of the ZIFs. Very recently, another approach by directly adding metal ions in the synthetic systems has been reported . After encapsulation of the metal ions inside the ZIFs, a reduction process is carried out so that metal ions would be reduced to metal NPs that stay inside the ZIFs.…”
Section: Strategies For Improving the Functionality Of Zifsmentioning
confidence: 99%
“…To evaluate the catalytic performance of the HNT@Au hybrid nanomaterial obtained, we chose the reduction of 4‐NP by NaBH 4 , which is the most used reaction to investigate the catalytic activity of metal nanoparticles in aqueous solution . The interest in this reaction is mainly due to the fact that 4‐NP is a common reactant in pharmaceuticals and can be a hazardous by‐product that is inhibitory and toxic in nature; the product of the reaction, 4‐aminophenol (4‐AP), is used for black‐and‐white films and for the production of acetaminophen.…”
Section: Resultsmentioning
confidence: 99%